Implications for Paradigm Shift in Nursing: A Critical Analysis of Thomas Kuhn's Revolutionary Science and Its Relevance to Nursing. (July 2019) - Younas, Ahtisham; Parsons, Karen
Abstract : By seeking answers to ontological and epistemological questions, nursing scholars explored the foundations of nursing and articulated the meaning of nursing science from various philosophical perspectives. This ongoing search for advancement and development of nursing aligns with the concept of "normal science" by Thomas Kuhn. Kuhn's science influenced nursing knowledge, resulting in the development of nursing metaparadigm and paradigms. Despite this influence, Kuhn's science's relevance for nursing science received a little scrutinization. This article presents a critical analysis of Kuhn's science and its influence on and relevance for nursing discipline and suggests implications for nursing knowledge development.